Factors Affecting the Debt Situation of Farmers in Phraya Banlue Subdistrict Administrative Organization, Lat Bua Luang District, Phra Nakhon Si Ayutthaya Province - โพธิ์เกษม, ภนิดา; รชตวัฒนกุล, สุวัจ; รชตวัฒนกุล, สนใจ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) study the factors of the indebtedness of farmers in Phraya Banlue Subdistrict Administrative Organization, Lat Bua Luang District, Phra Nakhon Si Ayutthaya Province, 2) study the indebtedness of farmers in Phraya Banlue Subdistrict Administrative Organization, Lat Bua Luang District, Phra Nakhon Si Ayutthaya Province, and 3) study the factors influencing the indebtedness of farmers in Phraya Banlue Subdistrict Administrative Organization, Lat Bua Luang District, Phra Nakhon Si Ayutthaya Province. The key informants, 302 people, collected data using interview forms and analyzed data using descriptive techniques. Quantitative research, a sample of 302 people, was obtained using the ready-made tables of Krezy and Morgan. Data were collected using questionnaires and analyzed by finding percentages, means, and standard deviations, and using logistic regression analysis.